2002
DOI: 10.1103/physrevb.65.094417
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the electronic contribution to the low-temperature specific heat of an Fe/Cr magnetic multilayer

Abstract: We measured the low temperature specific heat of a sputtered (F e 23Å /Cr 12Å ) 33 magnetic multilayer, as well as separate 1000Å thick Fe and Cr films. Magnetoresistance and magnetization measurements on the multilayer demonstrated antiparallel coupling between the Fe layers. Using microcalorimeters made in our group, we measured the specific heat for 4 < T < 30 K and in magnetic fields up to 8 T for the multilayer. The low temperature electronic specific heat coefficient of the multilayer in the temperature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…40 Experimentally it was found that the magnetic multilayers grown epitaxially shows an enhancement of the electronic contribution to the low-temperature specific heat. 41 Standard electronic band-structure calculations could not reproduce this enhancement, 42 which can be an evidence of the correlation effects. Our aim is to check whether the correlation effects considered in the EMTO-DMFT approach can lead to an essential renormalization of the density of states at the Fermi level N(E F ).…”
Section: E Feõcr Multilayermentioning
confidence: 99%
“…40 Experimentally it was found that the magnetic multilayers grown epitaxially shows an enhancement of the electronic contribution to the low-temperature specific heat. 41 Standard electronic band-structure calculations could not reproduce this enhancement, 42 which can be an evidence of the correlation effects. Our aim is to check whether the correlation effects considered in the EMTO-DMFT approach can lead to an essential renormalization of the density of states at the Fermi level N(E F ).…”
Section: E Feõcr Multilayermentioning
confidence: 99%
“…[62][63][64][65][66] Such a shift could reduce the probability of the largeangle phonon scattering events required to return L (T ) to the Sommerfeld value at high T, thereby requiring higher temperatures to finally reenter the WF regime. However, our calculations suggest that the shifts in phonon DOS required to explain the ∼ 20% reduction in L seen here are so large that they would drive deviations of the heat capacity away from bulk-like values, in contrast to experimental data showing very good agreement between bulk and even very thin Au and Cu films.…”
Section: -47mentioning
confidence: 99%
“…Focusing in the field of magnetic recording, a huge amount of experimental and theoretical work has been carried out during the last decade to seek novel approaches to construct advanced materials for ultrahigh density magnetic storage, with the aim of increasing the state-of-the-art beyond 1 Tbit/in 2( [8,[12][13][14][15] ) . Most approaches are focused on thin films or multilayers [16][17][18] and recently on slabs [19]. However, during the last decade has emerged the possibility to use clusters deposited on surfaces [20][21][22][23][24][25][26] to increase the recording density.…”
Section: Introductionmentioning
confidence: 99%